Dendritic Ni‐P‐Coated Melamine Foam for a Lightweight, Low‐Cost, and Amphipathic Three‐Dimensional Current Collector for Binder‐Free Electrodes. (18th September 2014) - Huang, Xiao‐lei; Xu, Dan; Yuan, Shuang; Ma, De‐long; Wang, Sai; Zheng, Huai‐yu; Zhang, Xin‐bo
<x xml:space="preserve">Abstract</x> A highly conductive 3D current collector that is dendritic, lightweight, and robust is synthesized for binder‐free electrodes in lithium‐ion batteries. It has excellent chemical/electrochemical stability in a wide voltage window (0–5 V) and robust mechanical behavior even after 600 cycles of compression. When active materials are grown in situ on the as‐obtained current collector, the resulting cycling stability and rate capability far exceed those of conventional electrodes and other 3D current collectors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>